Assessment of antioxidant resistance to thermal - oxidative degradation of stabilized polybutadiene binder. Issue 1 (December 2020) - Elsaka, Eslam; Elbasuney, Sherif; Elbeih, Ahmed; Mostafa, Hosam E.; Awad, Mahmoud E.; Elhedery, Tarek M.
Abstract: polybutadiene is the most common polymeric binder for composite solid propellants. This polymer suffers from oxidative degradation reactions on storing with deterioration in mechanical properties. Certain anti-oxidant materials can retard such reaction offering enhanced aging characteristics. In this study, two different primary antioxidants including phenol-based (AO2246) and amine-based (Flexzone 6H) were employed to stabilize polybutadiene polymer. Oxidation induction time (OIT) was evaluated using isothermal DSC. High OIT value means high resistance to oxidative degradation. The impact of anti-oxidant on mechanical properties was evaluated using shore A. Flexzone 6H significantly improved binder oxidative stability with an increase in OIT value by 20 folds with significant decrease in oxidation enthalpy. Flexzone 6H can offer enhanced resistance toward oxidative reactions; as it can act as efficient H atom donor to break down chain degradation reaction. Additionally, the three stabilized aromatic rings can capture free radicals. AO2246 enhanced the binder mechanical characteristics during aging at 80 0C using Shore A test. In the meantime, AO2246 could enhance the mechanical properties due to its integration into the polymeric matrix due to –OH functional groups. The two anti-oxidants demonstrated controversy effects. Whereas Flexzone 6H offered enhanced resistance to oxidative degradation; AO2246 offered enhanced mechanical properties.